INNOVATION IN IMPROVING THE QUALITY OF SALT PRODUCTION AT COASTAL AREAS: A LITERATUR STUDY - Siti Sumiati (International Conference on Coastal and Delta Areas, 2015)
Indonesia has avast coastal areas, but the fact still have to import salt from abroad. For that it is necessary improvements in yield and improve quality salt. Studies on salt production improvement efforts have been conducted by previous researchers.This paper aims to examine new technologies in the production processof salt includes Electrolysis, Evaporation and Geomembran etechnology. The results of this literature review can be used as a reference to the use of new technologies in the salt-producing areas in Indonesia.Keywords: Salt production, geomembrane, electrolysis, evaporation.